Cardioinformatics: the nexus of bioinformatics and precision cardiology. (4th December 2019) - Khomtchouk, Bohdan B; Tran, Diem-Trang; Vand, Kasra A; Might, Matthew; Gozani, Or; Assimes, Themistocles L
Abstract: Cardiovascular disease (CVD) is the leading cause of death worldwide, causing over 17 million deaths per year, which outpaces global cancer mortality rates. Despite these sobering statistics, most bioinformatics and computational biology research and funding to date has been concentrated predominantly on cancer research, with a relatively modest footprint in CVD. In this paper, we review the existing literary landscape and critically assess the unmet need to further develop an emerging field at the multidisciplinary interface of bioinformatics and precision cardiovascular medicine, which we refer to as 'cardioinformatics'.